Identificação de peptídeos miméticos a autoantígenos por phage display na Doença de Alzheimer - Oliveira Júnior, Luiz Carlos de (2012)
Alzheimer's Disease (AD) is the most important cause of dementia in the world.The involvement of the immune system in the pathogenic process has been shown by several studies including the description of autoantibodies (AAc) directed to targets in the central nervous system.It is not possible yet to further define what their exact involvement in AD is. In this study, using the methodology of Phage Display we sought to identify AAc specific to patients with the disease and to characterize their antigens using bioinformatics tools. We selected 10 patients with AD according to DSM-IV-TR and NINCDS ASRDA criteria and 10 healthy controls matched for age and sex.Using a library of peptides displayed on M13 phages, we performed biopanning, thus selecting 10 peptides recognized by IgG in sera from patients with AD. The probable epitopes were characterized and their involvement with AD was assessed in the literature.We found alignment with Neurexin 3β, PLK4, Neuroserpin, DNAJ, Mint-1/X11, units of the nicotinic acetylcholine receptor, Trombospondin-1, TRAF6, ACE, GDNF α3 receptor, PRUNE2 and CD44. The Phage display technology, combined with bioinformatics tools, has proven to be an interesting research methodology of AAb present in the serum of patients with AD and may provide new insights into disease mechanisms and therapeutic targets.